PENGEMBANGAN INSTRUMEN CRITICAL THINKING SKILLS SISWA SEKOLAH DASAR PADA PEMBELAJARAN ABAD 21 - Ni Nyoman Lisna Handayani (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
Developing critical thinking skills instruments aims to provide an overview of how the steps or ways that must be implemented by an educator in developing instruments as a measure of students' critical thinking skills, especially developing instruments in mathematics. The steps in developing a critical thinking skills measuring instrument are compiling instrument specifications, writing instruments, examining instruments, testing instruments, analyzing instrument items, improving instruments, and assembling instruments. Instrument specifications indicate the overall characteristics that an instrument must possess. Writing a problem is a step to describe indicators into questions whose characteristics are in accordance with the details in the grid that has been made. Instrument analysis activities were carried out on each item that had been scored using the dichotomy and politomy scoring model. Improving the test means making improvements to the questions that are not as expected. After all the questions that have been compiled are analyzed and corrected, the next step is to assemble the items into a single instrument.